IbM pelatihan supervisi manajerial bagi pengawas sekolah dasar di Kota Makassar - Muh. Ardiansyah; Ismail Tolla; Ratmawati Ratmawati (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The general objective of this activity is to improve the fulfillment of supervisor y managerial competencyimprovement needs which include aspects of management that are directly related to school efficiency and effectivenessincluding planning, coordination, implementation, assessment and development of educational human resource (HR)competencies and other resources . The target of community service activities is to make a real contribution to partners inmeeting the need to improve managerial supervision competencies for elementary school supervisors in Makassar City. Theamount of the managerial supervision quality conducted by supervisors to the principal of the primary school is largelydetermined by the quality of managerial supervision competencies. Therefore the solution adopted to improve supervisorsmanagerial competencies is to conduct "Managerial Supervision Training for Elementary School Supervisors in Makassar City".The results of the three days training obtained from the post-test assessment analysis conducted to participants concluded that:the competency of school supervisors who have attended managerial supervision training has increased above 35% from theaccumulation of the average value of the results of the pretest analysis from a score of 45 to a score of 80 after the posttest. Thisfigure showed an increase in managerial supervisory competencies for outstanding school supervisors. While the rest still needadditional reinforcement so that they can carry out managerial supervision well. The knowledge and skills gained in this trainingwill be applied in their schools in order to provide intensive guidance to the school principal in improving the quality of schoolmanagement services.